Worker’s Knowledge and Practices on Factors Influencing the Risk of Silica Dust Exposure in Lesotho Mines - Langwana, Vuyiseka (University of the Witwatersrand, Johannesburg, 2024)
Background Exposure to respirable crystalline silica (RCS) dust is a major occupational hazard linked to serious lung diseases, including silicosis, lung cancer, and pneumoconiosis, with mining accounting for a significant portion of these illnesses. Despite awareness of silica's health risks and efforts to control exposure, hazardous levels persist in industries like mining, quarrying, and mineral processing, where silica is found in materials such as quartzite, sandstone, and granite. Silicosis, an irreversible lung-scarring disease, remains prevalent among workers, particularly miners in Lesotho, where cases have slightly increased, underscoring the need for improved silica dust control measures. Although preventive controls exist, there is an urgent need to enhance silica exposure management in these high-risk environments. Aim This study aims to evaluate mine workers' knowledge, attitudes and practices regarding factors that increase the risk of silica dust exposure in selected mines in Lesotho. Methods The study employed a descriptive retrospective cross-sectional design with a quantitative approach. A record review guide was used to gather secondary data from the Southern Africa Tuberculosis and Health Systems Support (SATBHSS) project. This data was entered into Microsoft Excel, cleaned for accuracy, and analyzed in STATA software, version 17, using both descriptive and inferential statistics. The study focused on a sample of workers from 5 selected mines, chosen from 11 active mines in Lesotho, which extract various minerals. The selected mines were those engaged in mining diamonds, sandstone, and quarry materials. The study aimed to assess the knowledge, attitudes, and practices of mine workers regarding factors that elevate the risk of silica dust exposure in these mines. vi Results The study found that mine workers had good knowledge about certain Occupational Health and Safety (OHS) hazards, with high awareness of lung cancer (91%), noise levels (99%), and safety stressors (96%). However, 90% of workers lacked adequate knowledge on physical stressors in their workplaces. The average knowledge score was 13.43 (SD = 2.99), with scores ranging from 6 to 19 and a median of 14. Regarding preventive practices, 55% of workers reported the presence of health and safety strategies, 60% held regular safety meetings, and only 40% indicated regular dust and noise monitoring by employers. Additionally, 56% had health and safety representatives at work. Notably, 15% viewed the work as suitable only for the "brave," and 65% considered minor accidents a normal part of the job. The workforce was predominantly male (91%) with most having secondary education (79%), which may impact their understanding of training resources on crystalline silica exposure. Conclusion This study reveals that, while health and safety programs exist within mines to prevent exposure to respirable crystalline silica (RCS) dust, gaps in program implementation leave workers at risk for silicosis and other respiratory diseases. Mine workers generally had limited knowledge about managing RCS dust exposure, which leads to poor practices in dust control. The findings emphasize that engineering controls alone are insufficient, underscoring the need for a broader hierarchy of controls and improved administrative measures, including training and best practices. Only 46% of participants recognized air measurements as beneficial for controlling dust exposure. This study, the first of its kind in Lesotho, could inform national policies on silica dust exposure control. However, its findings may be less generalizable to similar mining contexts across Africa due to its retrospective, questionnaire-based design, which may introduce response bias. The study suggests that greater emphasis on knowledge, attitudes, and practices is essential to effectively reduce silica dust exposure in mines.
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; knowledge; practices; mines; silica dust exposure; SDG-3: Good health and well-being